Recommendation System for Mobile-Based Oil Palm Fertilization Period with Rainfall Prediction using ANN - Isnaini, Mei Nanda; Sari, Juni; Kusuma Wardhani, Kartina Diah; Tri Wahyuni, Retno (JOIV : International Journal on Informatics Visualization, 2025)
Weather conditions significantly affect human activities, including the oil palm plantation sector, which in practice considers weather and climate conditions. Oil palm is an annual crop that requires proper nutrition throughout the year. Plant nutrition through fertilization must be according to the specific needs of oil palms. Knowing the type of fertilizer, calculating the dosage, and evaluating the climatic characteristics significantly affect the effectiveness and efficiency of fertilization. According to one palm oil farmer, fertilization should ideally be done when the soil is moist or not during the dry season so plants can absorb fertilizers properly. If fertilization is ineffective, then the operational costs of plant maintenance to buy fertilizers become less efficient. Due to climate change, farmers often find it difficult to determine the optimal timing of fertilization. Therefore, rainfall prediction is essential. Thus, fertilization can run well and get maximum results. The recommendation system in this research includes a rainfall prediction system with machine learning methods and an Artificial Neural Network. The recommendation system is a mobile-based application that allows oil palm farmers to obtain information on the appropriate time to fertilize based on rainfall. The evaluation of rainfall prediction using ANN has the MSE value of 0.0019981 and the MAPE value of 9.355%. It can be concluded that the rainfall prediction model is working optimally. This system can be combined with harvesting forecasting and recommendations of oil palm plantation periods to become a monitoring system for oil palm productivity.